REFORMS IN THE FIGHT AGAINST DOMESTIC VIOLENCE (ON THE EXAMPLE OF THE REPUBLIC OF KAZAKHSTAN) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the reforms being implemented in the Republic of Kazakhstan in the field of combating domestic violence, their social and legal significance, as well as measures being taken in cooperation with international organizations. The study examines the law "On the Prevention of Domestic Violence", state programs and social initiatives adopted in the country. The results of the article show that a systematic approach to the prevention of domestic violence is being formed in Kazakhstan, but there are certain shortcomings at the practical stage.
Keywords: Crisis centers, Human centers, gender equality, harassment, violence, National Agency for Social Protection.